Performance Analysis of Table Driven and Event Driven Protocols for Voice and Video Services in MANET - Haque Nawaz; Husnain Mansoor Ali (JISR on Computing, 2015)
This research paper encompasses the performance analysis of table driven and event driven routing protocols by using voice and video traffic in mobile Adhoc network (MANET). Particularly, OLSR (table driven) and DSR (Event driven) protocol are considered. The nodes of MANET establish the connections with each other energetically and can move freely in any direction. In mobile Adhoc network, environment event driven and table driven protocols have significant subject matter of study. There is a mobility issue which matters the service performance due to breakage and renewal of links of mobile nodes. Protocols performance has significance on overall performance of MANET. The aim of this study is to present the performance analysis of selected routing protocols by varying the node densities and WLAN physical characteristics. The voice and video traffic applications are configured discretely by using OLSR and DSR in scenarios. Moreover, for the performance observation the parameters are jitter, traffic received, traffic sent, end-to-end delay, traffic load, and throughput. The simulations have been carried out through OPNET 14.5 modeller tool and results has been analysed.